2021
DOI: 10.1021/acs.jpclett.1c02978
|View full text |Cite
|
Sign up to set email alerts
|

Packing-Shape Effects of Optical Properties in Amplified Spontaneous Emission through Dynamics of Orbit–Orbit Polarization Interaction in Hybrid Perovskite Quantum Dots Based on Self-Assembly

Abstract: This paper reports packing-shape effects of amplified spontaneous emission (ASE) through orbital polarization dynamics between light-emitting excitons by stacking perovskite (MAPbBr3) quantum dots (QDs sized between 10 nm and 14 nm) into rod-like and diamond-like aggregates. The rod-like packing shows a prolonged photoluminescence (PL) lifetime (184 ns) with 3 nm red-shifted peak (525 nm) as compared to the diamond-like packing (PL peak, 522 nm; lifetime, 19 ns). This indicates that the rod-like packing forms … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 57 publications
(73 reference statements)
0
1
0
Order By: Relevance
“…The orbital momentum provides the precondition to realize the interaction between incident electromagnetic waves and photoinduced polarizations when electrons are excited by high-power laser excitation, leading to multi-photon absorption up-conversion ASE. Furthermore, our previous work has found that long-range orbital-orbital polarization interactions occur at the generation of ASE in perovskite, which provides the necessary conditions for coherent interactions between light-emitting excitons through polarization-dependent ASE studies [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 97%
“…The orbital momentum provides the precondition to realize the interaction between incident electromagnetic waves and photoinduced polarizations when electrons are excited by high-power laser excitation, leading to multi-photon absorption up-conversion ASE. Furthermore, our previous work has found that long-range orbital-orbital polarization interactions occur at the generation of ASE in perovskite, which provides the necessary conditions for coherent interactions between light-emitting excitons through polarization-dependent ASE studies [18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 97%